Draft Seventh Five Year Plan 1985-90 and Annual Plan 1985-86 Volume- III Government of Manipur - Planning Commission (Planning Commission, 1985)
Outlay & Expenditure(Head of Development) Outlay & Expenditure(Development Schemes/Projects Targets of Production & Physical Achievements Outlay & Expenditure(Minimum Needs Programme) Outlay & Expenditure (Centrally Sponsored Scheme) State Plan Outlays Under Tribal Sub- Plan Target & Physical Achievements under sub-plan Speed Component Plan for Scheduled castes.
Planning Department, Government of Manipur